Tumor regression rate, PD-L1 expression, pembrolizumab/nab-paclitaxel–based regimens, squamous cell carcinoma, and comorbidities were independently associated with efficacy of neoadjuvant chemoimmunotherapy in non-small cell lung cancer - Hu, Xingsheng; Hu, Chunhong; Liu, Xianling; Ma, Fang; Xie, Junpeng; Zhong, Ping; Tang, Chenxi; Fan, Dan; Gao, Yuan; Feng, Xiang; Ding, Mengge; Li, Dezhi; et al. (Frontiers in Oncology, 2023)
Background: Neoadjuvant chemoimmunotherapy (NCIO) is more effective than neoadjuvant immunotherapy alone for pathological response in non-small cell lung cancer (NSCLC) patients, but processes for determining patient suitability for its implementation are not clear. We aimed to identify the most relevant factors and build a convenient model to select NSCLC patients who would benefit most from NCIO. Methods: We retrospectively collected the clinical data of patients with locally advanced NSCLC who received NCIO followed by surgery at our institution between January 2019 and July 2022. Results: A total of 101 eligible stage IIB-IIIC NSCLC patients were included. After NCIO, all patients successfully underwent surgical resection. A total of 46.53% (47/101) of patients achieved pathological complete response (pCR), and 70.30% (71/101) achieved major pathologic response (MPR). We determined that tumor regression rate (adjusted OR=12.33), PD-L1 expression (adjusted OR=9.66), pembrolizumab/nab-paclitaxel-based regimens (adjusted OR=4.92) and comorbidities (adjusted OR=0.16) were independently associated with pCR rate (all P<0.05). Tumor regression rate (adjusted OR=8.45), PD-L1 expression (adjusted OR=5.35) and presence of squamous cell carcinoma (adjusted OR=7.02) were independently associated with MPR rate (all P<0.05). We established and validated an easy-to-use clinical model to predict pCR (with an area under the curve (AUC) of 0.848) and MPR (with an AUC of 0.847). Of note, the present study showed that CD4+ T cell count/rate and total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) levels in the peripheral blood of pre-NCIO patients were also significantly correlated with pathological response in univariate analyses. Conclusions: The tumor regression rate, PD-L1 expression, pembrolizumab/nab-paclitaxel-based regimens, presence of squamous cell carcinoma, and comorbidities were the main influential factors for incidence of pCR/MPR in patients with stage IIB-IIIC NSCLC in present study. Through predictive models, we can predict who will benefit most from NCIO prior to the emergence of clinical outcomes in locally advanced NSCLC.